Toxicity and Antioxidant Activity of Teabags of Mangrove Lenggadai (Bruguiera parviflora) and Stevia (Stevia rbaudiana Bertoni) Leaves - Andjelie, Tiara; Lubis, Minda Sari; Nasution, Haris Munandar; Rani, Zulmai (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2025)
Introduction: Mangrove plants are known to have a lot of potential as medicine. One of the most commonly found mangroves is the lenggadai mangrove (Bruguiera parviflora).  Utilization of herbal drinks is made to prevent the onset of various diseases. The mixed teabag of mangrove lenggadai leaves and stevia leaves (Stevia rbaudiana bertoni) is named Mangrove Lenggadai Stevia (MLS) teabag. Aims: the purpose of this study is to see which MLS teabag formulation has good antioxidant activity and toxicity activity. Methods: The research conducted was experimental in nature. The data collected are quantitative and qualitative data which are taken from the results of sample collection, physical characteristics of MLS teabag quality, phytochemical screening of simplisia, antioxidant activity test using DPPH (1,1-Diphenyl-2-Picrylhydrazyl) method, toxicity test using Brine Shrimp Lethality Test (BSLT) method on Artemia salina Leach shrimp larvae, stability and hedonic level Result: MLS teabags have characteristics according to the quality requirements of SNI 4324:2014. The results of determining the antioxidant activity of MLS teabags obtained an IC50 value of 13.38 µg/mL. The results of the toxicity test of MLS teabags obtained an LC50 value of 8.74 µg/mL. Conclusion: MLS tea bags have physical quality characteristics that meet the requirements of SNI 4324: 2014 and have the potential as antioxidants and toxicity activity against Artemia salina Leach.